Varietal features of lectin activity of soft winter wheat (Triticum aestivum L.) at the early stages of ontogenesis - Л. В. Чеботарьова (Plant Varieties Studying and Protection)
Purpose. To study the dynamics of soft winter wheat lectin activity in caryopsis and at the early stages of ontogenesis of varieties developed by Poltava State Agrarian Academy as well as investigate varietal differences depending on dynamic pH medium. Methods. Laboratory analysis, method of hemagglutination reaction, analytical approach, statistical evaluation. Results. A change in lectin activity was determined in samples of 14 soft winter wheat varieties in caryopsis and at the early stages of ontogenesis (on the third, seventh, tenth and twelfth day of seedlings emergence). High lectin activity was observed in samples of seven and ten days seedlings. This could be evidence of active participation of proteins in physiological and biochemical processes at the time of emerging wheat tillering node that can be important in forming adaptive reactions to stress. Wheat lectin activity variation for рН ranging between 4,0 and 8,0 that depended on a variety was defined for the first time. Conclusions. According to hemagglutination ability of wheat lectins, all varieties were divided into three groups: of high ability – 4 varieties, middle – 9 varieties, low – 1 variety. Varietal variability for the investigated trait can be used in breeding programs as marker trait. In most varieties variation of hemagglutination was observed at dilutions ranging between 1:2 and 1:256. Availability of two lectin agglutination peaks in acidic and alkaline media for seedlings was fixed.